Golden Rice is an effective source of vitamin A - Tang, Guangwen; Qin, Jian; Dolnikowski, Gregory G; Russell, Robert M; Grusak, Michael A (The American journal of clinical nutrition, 2009)
Genetically engineered "Golden Rice" contains up to 35 microg beta-carotene per gram of rice. It is important to determine the vitamin A equivalency of Golden Rice beta-carotene to project the potential effect of this biofortified grain in rice-consuming populations that commonly exhibit low vitamin A status. The objective was to determine the vitamin A value of intrinsically labeled dietary Golden Rice in humans. Golden Rice plants were grown hydroponically with heavy water (deuterium oxide) to generate deuterium-labeled [2H]beta-carotene in the rice grains. Golden Rice servings of 65-98 g (130-200 g cooked rice) containing 0.99-1.53 mg beta-carotene were fed to 5 healthy adult volunteers (3 women and 2 men) with 10 g butter. A reference dose of [13C10]retinyl acetate (0.4-1.0 mg) in oil was given to each volunteer 1 wk before ingestion of the Golden Rice dose. Blood samples were collected over 36 d. Our results showed that the mean (+/-SD) area under the curve for the total serum response to [2H]retinol was 39.9 +/- 20.7 microg x d after the Golden Rice dose. Compared with that of the [13C10]retinyl acetate reference dose (84.7 +/- 34.6 microg x d), Golden Rice beta-carotene provided 0.24-0.94 mg retinol. Thus, the conversion factor of Golden Rice beta-carotene to retinol is 3.8 +/- 1.7 to 1 with a range of 1.9-6.4 to 1 by weight, or 2.0 +/- 0.9 to 1 with a range of 1.0-3.4 to 1 by moles. Beta-carotene derived from Golden Rice is effectively converted to vitamin A in humans. This trial was registered at clinicaltrials.gov as NCT00680355.